Sleep homeostasis in the rat is preserved during chronic sleep restriction. - Leemburg, S; Vyazovskiy, V; Olcese, U; Bassetti, C; Tononi, G; Cirelli, C (2010)
Sleep is homeostatically regulated in all animal species that have been carefully studied so far. The best characterized marker of sleep homeostasis is slow wave activity (SWA), the EEG power between 0.5 and 4 Hz during nonrapid eye movement (NREM) sleep. SWA reflects the accumulation of sleep pressure as a function of duration and/or intensity of prior wake: it increases after spontaneous wake and short-term (3-24 h) sleep deprivation and decreases during sleep. However, recent evidence suggests that during chronic sleep restriction (SR) sleep may be regulated by both allostatic and homeostatic mechanisms. Here, we performed continuous, almost completely artifact-free EEG recordings from frontal, parietal, and occipital cortex in freely moving rats (n = 11) during and after 5 d of SR. During SR, rats were allowed to sleep during the first 4 h of the light period (4S(+)) but not during the following 20 h (20S(-)). During the daily 20S(-) most sleep was prevented, whereas the number of short (<20 s) sleep attempts increased. Low-frequency EEG power (1-6 Hz) in both sleep and wake also increased during 20S(-), most notably in the occipital cortex. In all animals NREM SWA increased above baseline levels during the 4S(+) periods and in post-SR recovery. The SWA increase was more pronounced in frontal cortex, and its magnitude was determined by the efficiency of SR. Analysis of cumulative slow wave energy demonstrated that the loss of SWA during SR was compensated by the end of the second recovery day. Thus, the homeostatic regulation of sleep is preserved under conditions of chronic SR.